Carbon Quantum Dots for Biomedical Applications: Review and Analysis - Azam, Nayab; Najabat Ali, Murtaza; Javaid Khan, Tooba (Frontiers in Materials, 2021)
Carbon quantum dots (CQDs) are a new type of nano-carbons that are currently favored over semiconductor quantum dots (QDs) because of their solubility, low toxicity, eco-friendliness, and cheap and facile synthesis giving desired optical characteristics. Moreover, their physiochemical properties can be controlled by their synthetic route. CQDs can emit fluorescence in the range from the UV to the near-infrared (NIR) region, making them suitable for biomedical applications. Fluorescence in these nano-carbon atoms can be tuned by varying the excitation wavelength. As of now, CQDs have been used in various applications such as in bioimaging, biosensing, electrochemical biosensing, drug delivery, gene delivery, photodynamic therapy in the treatment of cancers, pharmaceutical formulations, and treating inflammation. This article highlights the current progress and advancement of CQDs with focus on their synthetic routes, chemical and optical properties, and biomedical applications along with new perceptions in this interesting and promising field.